2021
DOI: 10.1016/j.cyto.2021.155654
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-6 in the commitment of T cell subsets

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 105 publications
2
26
0
Order By: Relevance
“…STAT3 plays an important role in solid tumors, including in KRAS-induced pancreatic tumorigenesis ( Corcoran et al, 2011 ). IL-6 is an important canonical activator of STAT3 and the IL-6/STAT3 axis promotes the expansion of immunosuppressive cells while altering the balance of T-cell subsets ( Mace et al, 2018 ; Korn & Hiltensperger, 2021 ). Notably, IL-6 and activated pY705-STAT3 are evident in CAFs in human PDAC samples and isolated CAFs ( Mace et al, 2018 ); however, the role of STAT3 signaling from CAFs within the context of de novo pancreatic tumorigenesis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 plays an important role in solid tumors, including in KRAS-induced pancreatic tumorigenesis ( Corcoran et al, 2011 ). IL-6 is an important canonical activator of STAT3 and the IL-6/STAT3 axis promotes the expansion of immunosuppressive cells while altering the balance of T-cell subsets ( Mace et al, 2018 ; Korn & Hiltensperger, 2021 ). Notably, IL-6 and activated pY705-STAT3 are evident in CAFs in human PDAC samples and isolated CAFs ( Mace et al, 2018 ); however, the role of STAT3 signaling from CAFs within the context of de novo pancreatic tumorigenesis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, anti-TNF therapy failed to provide significant protective effect in clinical trials [ 17 ], even though no complications were reported [ 18 , 19 ]. IL-6, on the other hand, orchestrates differentiation and commitment of different T-cell subsets, especially Th17-cells [ 20 ]. Th17-cells are the gatekeepers of mucosal homeostasis and are involved in neutrophil recruitment, thus, contributing to severe asthma [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis is based on previous research in mice that indicates that Salmonella -specific Th17 cells can recognize Salmonella flagellin ( Lee et al, 2012 ) and that Salmonella Flagellin antigen has also shown an intrinsic ability to elicit IL-1 and IL-6 production ( Salazar-Gonzalez and McSorley, 2005 ; Mizel and Bates, 2010 ). Moreover, it has been reported that IL-6 is a non-redundant differentiation factor for Th17 cells ( Korn and Hiltensperger, 2021 ) in which significantly increased levels of IL-6 can promote the generation of Th17 cells ( Hou et al, 2014 ) and result in IL-6 and IL-17 cytokines. So, the recognition of the vaccine’s flagellin by TLR 5 and its ability to induce significant IL-6 mRNA may be the force driving the Th17 response against Salmonella in the cecal tonsils during S .…”
Section: Discussionmentioning
confidence: 99%